Retinoic acid induces sodium/iodide symporter gene expression and radioiodide uptake in the MCF-7 breast cancer cell line - Kogai, Takahiko (The National Academy of Sciences, 2000)
The sodium/iodide symporter (NIS) stimulates iodide uptake in normal lactating breast, but is not known to be active in nonlactating breast or breast cancer. We studied NIS gene regulation and iodide uptake in MCF-7 cells, an estrogen receptor (ER)-positive human breast cancer cell line. All-trans retinoic acid (tRA) treatment stimulated iodide uptake in a time- and dose-dependent fashion up to ≈9.4-fold above baseline. Stimulation with selective retinoid compounds indicated that the induction of iodide uptake was mediated by retinoic acid receptor. Treatment with tRA markedly stimulated NIS mRNA and immunoreactive protein (≈68 kDa). tRA stimulated NIS gene transcription ≈4-fold, as shown by nuclear run-on assay. No induction of iodide uptake was observed with RA treatment of an ER-negative human breast cancer cell line, MDA-MB 231, or a normal human breast cell line, MCF-12A. The iodide efflux rate of tRA-treated MCF-7 cells was slow (t(1/2) = 24 min), compared with that in FRTL-5 thyroid cells (t(1/2) = 3.9 min), favoring iodide retention in MCF-7 cells. An in vitro clonogenic assay demonstrated selective cytotoxicity with (131)I after tRA stimulation of MCF-7 cells. tRA up-regulates NIS gene expression and iodide uptake in an ER-positive breast cancer cell line. Stimulation of radioiodide uptake after systemic retinoid treatment may be useful for diagnosis and treatment of some differentiated breast cancers.